Planning of Medium-Voltage Electric Power Distribution Systems through a Scatter Search Algorithm - Padua, S. G. Bd.; Cossi, A. M. [UNESP]; Mantovani, J. R. S. [UNESP] (Ieee-inst Electrical Electronics Engineers Inc, 2015)
In this paper the problem of Planning Electric Power Distribution Systems (PEPDS) of Medium Voltage is formulated as a mixed integer nonlinear programming (MINLP) model. For solving this model the scatter search (SS) algorithm is proposed, an evolutionary search technique which according to the specialized literature has not yet been used for solving this problem. The main contribution of this work is the description of the five basic stages of SS for the PEPDS problem. The method was applied to 54 and 417 busbars from testing systems found in the specialized literature.
Keywords: Distribution System; Planning; Scatter Search; Combinatorial Optimization